Dosimetric study of fetal exposure to uniform magnetic fields at 50 Hz. Issue 8 (29th September 2014) - Liorni, Ilaria; Parazzini, Marta; Fiocchi, Serena; Douglas, Mark; Capstick, Myles; Gosselin, Marie‐Christine; Kuster, Niels; Ravazzani, Paolo
<x xml:space="preserve">Abstract</x> In this paper, fetal exposure to uniform magnetic fields (MF) with different polarizations is quantified at 50 Hz. Numerical computations were performed on high‐resolution pregnant models at 3, 7, and 9 months of gestational age (GA), that distinguish a high number of fetal tissues. Fetal whole‐body and tissue‐specific induced electric fields (E) and current densities (J) were analyzed as a function of both the extremely low frequency magnetic field (ELF‐MF) polarization and GA. Additionally, the induced field variation due to changes in fetal position was analyzed by means of two new pregnant models. The uncertainty budget due to the grid resolution was also calculated. Finally, the compliance of the fetal exposure to the ICNIRP Guidelines was checked. A fetal exposure matrix was built at 50 Hz, which could be used to further investigate possible interaction mechanisms between ELF‐MF and the associated health risk. Some specific findings were: (1) the induced fields increased with GA; (2) the maxima E were found in skin and fat tissues at each GA; (3) fetal tissue‐specific exposure was modified as a function of GA and polarization; (4) the change of the fetal position in the womb significantly modified the induced E in some fetal tissues; (5) the induced fields were in compliance with ICNIRP Guidelines and the results were quite below the permitted threshold limit. Bioelectromagnetics 35:580–597, 2014. © 2014 Wiley Periodicals, Inc.